La Problemática Del Embarazo En Las Adolescentes Y La Acción Del Trabajador Social En La Prevención. - Fierro Pineda, Lorena María (2016)
This research work entitled " THE PROBLEM OF ADOLESCENT PREGNANCY AND ACTION SOCIAL WORKER IN THE PREVENTION " is intended to explain how the Social Worker involved deal with this problem , presented in Educational Establishments , whereas education sex is very important as it allows the comprehensive development of adolescents who are currently instructing . The specific objectives of the research, provided to identify the concepts related to the types of sex education that led to the initiation of adolescent early sexual life , allowing them to recognize the new responsibilities as pregnant teens have to assume. The main findings from field research that was aimed at pregnant teenagers in the Provincial General Hospital Isidro Ayora, determine that the youth do not have a support program or project on sexual education that is aimed at teenagers of different educational institutions in general, this is that the level of participation of the Departments of Guidance and Student Welfare does not provide in its entirety with the felt needs and required by teenagers especially girls who are in a state of gestation. It is noteworthy that the thematic on sex education is provided to students through / teachers are not adequate as it should facilitate knowledge according to their age and the same should be thoughtfully analyzed and treated superficially and thus able to decrease the rate of early pregnancies. That is why it is essential that adolescents receive lectures on prevention and family planning as many of them are not well informed and still unaware of the risks and consequences that could result in early pregnancy. Finally, the proposal raised consisting of a training program on responsible sexuality is.